Analysis of single nucleotide polymorphisms of the metabotropic glutamate receptors in a transgender population - Fernández, Rosa; Ramírez, Karla; Lorente-Bermúdez, Roberto; Gómez-Gil, Esther; Mora, Mireia; Guillamon, Antonio; Pásaro, Eduardo (Frontiers in Endocrinology, 2024)
Gender incongruence (GI) is characterized by a marked incongruence between an individual’s experienced/expressed gender and the assigned sex at birth. It includes strong displeasure about his or her sexual anatomy and secondary sex characteristics. In some people, this condition produces a strong distress with anxiety and depression named gender dysphoria (GD). This condition appears to be associated with genetic, epigenetics, hormonal as well as social factors. Given that L-glutamate is the major excitatory neurotransmitter in the central nervous system, also associated with male sexual behavior as well as depression, we aimed to determine whether metabotropic glutamate receptors are involved in GD. We analyzed 74 single nucleotide polymorphisms located at the metabotropic glutamate receptors (mGluR1, mGluR3, mGluR4, mGluR5, mGluR7 and mGluR8) in 94 transgender versus 94 cisgender people. The allele and genotype frequencies were analyzed by χ2 test contrasting male and female cisgender and transgender populations. The strength of the associations was measured by binary logistic regression, estimating the odds ratio (OR) for each genotype. Measurement of linkage disequilibrium, and subsequent measurement of haplotype frequencies were also performed considering three levels of significance: P≤0.05, P≤0.005 and P≤0.0005. Furthermore, false positives were controlled with the Bonferroni correction (P≤0.05/74=0.00067). Results: After analysis of allele and genotypic frequencies, we found twenty-five polymorphisms with significant differences at level P≤0.05, five at P≤0.005 and two at P≤0.0005. Furthermore, the only two polymorphisms (rs9838094 and rs1818033) that passed the Bonferroni correction were both related to the metabotropic glutamate receptor 7 (mGluR7) and showed significant differences for multiple patterns of inheritance. Moreover, the haplotype T/G [OR=0.34 (0.19-0.62); P<0.0004] had a lower representation in the transgender population than in the cisgender population, with no evidence of sex cross-interaction. Conclusion: We provide genetic evidence that the mGluR7, and therefore glutamatergic neurotransmission, may be involved in GI and GD.